Regulatory peptides in the urinary bladder of two genera of Antarctic Teleosts - MASINI, MARIA ANGELA; M. STURLA; P. PRATO; P. ROMANO; B. UVA (Polar Biology, 1999)
Somatostatin 14, prolactin, atrial natriuretic peptide, galanin and urotensin II were found using immunohistochemistry in the urinary bladders of the Antarctic ®shes Trematomus bernacchii (Nototheniidae) and Chionodraco hamatus (Channichthyidae) caught in the Ross Sea. The urinary bladders of the two species showed a dierent histology in the epithelial layer. In T. bernacchii the epithelium comprises a single type of columnar cells, while in C. hamatus the columnar cells are restricted to the ventral portion of the bladder, and the dorso-lateral region is lined by cuboidal cells. No dierence in the intensity of the immunostaining was observed in the two cell types; the only variation was a dierent distribution of the immunoreactions, which were present in the whole cytoplasm in the cuboidal cells and restricted to the apical and/or basal portion of the columnar cells.